Pengaruh Electronic Word of Mouth (e-WOM) Valence dan Perceived Brand Qualityterhadap Online Purchase Intention Produk Sabun BDL (Studi Kasus Pada Endorsement Sabun BDL Fadil Jaidi di Tiktok) - Rennisa Anjani Saputra; Ridfa Chairani (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.The growing discussions about facial beauty on social media, along with the increasing trend of usingskincare products, have encouraged companies to utilize digital marketing strategies, one of which is bycollaborating with influencers to expand market reach and increase consumer purchases. BDL Soap is abeauty soap product that promotes itself through an endorsement by Fadil Jaidi on TikTok. This study aimedto examine the impact of Electronic Word of Mouth (e-WOM) Valence and Perceived Brand Quality on OnlinePurchase Intention. The study involved 267 respondents who are active TikTok social media users and haveobserved Fadil Jaidi's endorsement content of BDL Soap. The method used is Structural Equation Modeling(SEM) with a Partial Least Square (PLS) approach. The analysis results showed that Electronic Word ofMouth (e-WOM) Valence and Perceived Brand Quality significantly influence Online Purchase Intention, with a value of 67.4%. Keywords: e-WOM Valance, Perceived Brand Quality, Online Purchase Intention